Tension to passively cinch the mitral annulus through coronary sinus access: an ex vivo study in ovine model - Bhattacharya, Shamik (2014)
INTRODUCTION: The transcatheter mitral valve repair (TMVR) technique utilizes a stent to cinch a segment of the mitral annulus (MA) and reduces mitral regurgitation. The cinching mechanism results in reduction of the septal-lateral distance. However, the mechanism has not been characterized completely. In this study, a method was developed to quantify the relation between cinching tension and MA area in an ex vivo ovine model. METHOD: The cinching tension was measured from a suture inserted within the coronary sinus (CS) vessel with one end tied to the distal end of the vessel and the other end exited to the CS ostium where it was attached to a force transducer on a linear stage. The cinching tension, MA area, septal-lateral (S-L) and commissure-commissure (C-C) diameters and leakage was simultaneously measured in normal and dilated condition, under a hydrostatic left ventricular pressure of 90 mmHg. RESULTS: The MA area was increased up to 22.8% after MA dilation. A mean tension of 2.1 ± 0.5 N reduced the MA area by 21.3 ± 5.6% and S-L diameter by 24.2 ± 5.3%. Thus, leakage was improved by 51.7 ± 16.2 % following restoration of normal MA geometry. CONCLUSION: The cinching tension generated by the suture acts as a compensation force in MA reduction, implying the maximum tension needed to be generated by annuloplasty device to restore normal annular size. The relationship between cinching tension and the corresponding MA geometry will contribute to the development of future TMVR devices and understanding of myocardial contraction function.